'Organized crime' in Russia and Eastern Europe: from rhetoric to reality - Rawlinson, Patricia (Henry Stewart Talks, 2008)
Defining organized crime, The nature of organized crime in Russia and Eastern Europe, A brief history of crime, Glasnost, perestroika & beyond, Growth of criminality, Russia and the market, From communism to capitalism, Protection and entrepreneurship, Rise and fall of the oligarch, Crime as a consequence of capitalism, The road to authoritarianism, Human (sex) trafficking, Trafficking entrepreneurs and actors, The Baltic States, 'New Europe', Transnational crime: target states, Law enforcement and transnational crime, Lessons to be learned
Archived at 2022/04/03